Menu

#2353 rootscontract anomaly

open
nobody
5
2012-11-18
2012-02-06
No

ex: (sqrt(2)+1)^(2/3)$

rootscontract(ex)=> (sqrt(2)+1)^(2/3) <<< does nothing
rootscontract(2*ex) => 2*(2^(3/2)+3)^(1/3) <<< squares the inner expression

Though the documentation is not explicit about what it should do in this case (it only talks about products of roots, not about powers of roots), the second behavior is more useful -- if it isn't provided by rootscontract, it should be provided by *some* function.

Practical result of this anomaly:

rootscontract( (2^(3/2)+3)^(1/3)-(sqrt(2)+1)^(2/3) ) => 0 (I don't know any other way to do this simplification in Maxima)
but
rootscontract( -( (2^(3/2)+3)^(1/3)-(sqrt(2)+1)^(2/3) )) => remains unsimplified

Discussion

  • Aleksas

    Aleksas - 2012-02-07

    (%i1) r:(sqrt(2)+1)^(2/3)$

    (%i2) r=expand(r^3)^(1/3);
    (%o2) (sqrt(2)+1)^(2/3)=(2^(3/2)+3)^(1/3)

    (%i3) 2*r=expand((2*r)^3)^(1/3);
    (%o3) 2*(sqrt(2)+1)^(2/3)=(2^(9/2)+24)^(1/3)

    Aleksas

     
  • Aleksas

    Aleksas - 2012-02-07

    How simplify
    (%i1) ex:(sqrt(2)+1)^(2/3);
    (%o1) (sqrt(2)+1)^(2/3)

    (%i2) ex^3=expand(ex^3);
    (%o2) (sqrt(2)+1)^2=2^(3/2)+3
    (%i3) %^(1/3);
    (%o3) (sqrt(2)+1)^(2/3)=(2^(3/2)+3)^(1/3)

    Other example. How simplify
    (%i4) ex:4*atan(1/5)-atan(1/239);
    (%o4) 4*atan(1/5)-atan(1/239)

    (%i5) tan(ex)=trigexpand(trigexpand(tan(ex)));
    (%o5) tan(4*atan(1/5)-atan(1/239))=1
    (%i6) atan(%);
    (%o6) 4*atan(1/5)-atan(1/239)=%pi/4

    Aleksas D

     
  • Aleksas

    Aleksas - 2012-02-07

    Next example.
    see http://www.math.utexas.edu/pipermail/maxima/2012/027666.html
    How simplify
    (%i7) ex:sqrt(1-x^2)/(2-2*x^2)$

    (%i8) assume(abs(x)<1)$
    We define transformation funkcion f(t) and its inverse g(t):
    (%i9) f(t):=(2*t)^2$ g(t):=sqrt(t)/2$
    (%i11) assume(t>0)$
    (%i12) f(g(t)); g(f(t));
    (%o12) t
    (%o13) t

    (%i14) f(ex)=ratsimp(f(ex));
    (%o14) (4*(1-x^2))/(2-2*x^2)^2=-1/(x^2-1)
    (%i15) g(%);
    (%o15) sqrt(1-x^2)/(2-2*x^2)=1/(2*sqrt(1-x^2))

    Aleksas D

     

Log in to post a comment.